State Legal Thought in Russia 19th - Early 20th Centuries in Monographs and Scientific Papers: The Experience of Systemic Examination - Apolsky, Evgeny A.; Mamychev, Alexey Yu.; Mordovtsev, Andrey Yu.; Hasanova, Zamira G.; Shalyapin, Sergey O. (Journal of History Culture and Art Research, 2018)
The paper presents the results of the next stage of a comprehensive study concerning Russian state-legal doctrines in the 19th and early 20th centuries, taken in the triune of the external form of their expression: in dissertations, in monographs and in scientific papers of the periodical legal press. The authors analyzed the content and results of publication of monographs and the most famous papers published by pre-revolutionary Russian political scientists on key aspects of the state (constitutional) law science. Data are presented on the main priority areas of research, poorly developed fields of public law science, the laws of genesis and evolution, respectively, of monographic and periodical state-legal doctrines. The methodology proposed for the identification, analysis and general theoretical evaluation of state-legal doctrines has every reason to be applied for obtaining comprehensive knowledge of other branch pre-revolutionary legal doctrines.